2021
DOI: 10.1002/jdd.12598
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of orthodontic residents’ performance and attitudes using 2D, 3D, and virtual reality surgical simulation methods

Abstract: Purpose Advances in virtual reality technology for surgical simulation methods may improve diagnosis and treatment planning of complex orthognathic surgery cases. The objectives were to assess orthodontic residents’ performance and attitudes when treatment planning orthognathic surgery cases using two‐dimensional (2D) digital, three‐dimensional (3D) digital, and virtual reality (VR) surgical simulations. Methods The study had a mixed methods study design involving 20 graduate orthodontic residents. Their previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…A previous study has assessed orthodontic residents’ performance and attitudes when treatment planning orthognathic surgery cases using 2D digital, 3D digital, and VR surgical simulations and demonstrate that simulation methods of increased fidelity (3D and VR) are appropriate alternatives to 2D conventional orthognathic surgical simulation methods when combined with traditional records, [15] which was in accordance with our results. Another study on education during surgical procedures and related clinical anatomy in a VR workspace showed that use of VR technology with a live communication tool could be an alternative teaching method and its overall advantages are a closer look at the slides/monitor and concurrent observation of the multiple assets in various directions by multiple attendees [16] …”
Section: Discussionsupporting
confidence: 91%
“…A previous study has assessed orthodontic residents’ performance and attitudes when treatment planning orthognathic surgery cases using 2D digital, 3D digital, and VR surgical simulations and demonstrate that simulation methods of increased fidelity (3D and VR) are appropriate alternatives to 2D conventional orthognathic surgical simulation methods when combined with traditional records, [15] which was in accordance with our results. Another study on education during surgical procedures and related clinical anatomy in a VR workspace showed that use of VR technology with a live communication tool could be an alternative teaching method and its overall advantages are a closer look at the slides/monitor and concurrent observation of the multiple assets in various directions by multiple attendees [16] …”
Section: Discussionsupporting
confidence: 91%
“…For example, data from brain imaging of patients during pain can be visualized by students in virtual reality to have a more immersive educational experience (DaSilva et al 2014). The same applies with orthognathic surgical simulation methods when combined with traditional records, showing positive attitudes from the students toward higher-fidelity tools concerning visualization, manipulation, and enjoyment of the task (Sytek et al 2021). When applied directly in the clinic, the best mixed reality technologies are the ones that do not interfere with the dentist-patient communication and improve our ability to assess patients' conditions with more precision.…”
Section: Augmented Reality and Virtual Realitymentioning
confidence: 99%
“…[16][17][18][19][20][21][22] In dental education, immersive VR has been shown to be as effective as conventional learning methods which can improve student performance in orthognathic surgical prediction and delivery of injections with increase in learner satisfaction. [23][24][25][26][27][28][29][30] Additionally, there may be added bene-fits for student learning of anatomy and 3D imaging and radiology concepts by combining head and neck anatomy, CBCT images and immersive VR technology to improve the educational experience and knowledge retention for dental students. When Radianti et al conducted a systematic review regarding usage of VR in higher education, they found that evaluation of VR applications has primarily focused on usability of the VR applications instead of learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In dental education, immersive VR has been shown to be as effective as conventional learning methods which can improve student performance in orthognathic surgical prediction and delivery of injections with increase in learner satisfaction 23–30 . Additionally, there may be added benefits for student learning of anatomy and 3D imaging and radiology concepts by combining head and neck anatomy, CBCT images and immersive VR technology to improve the educational experience and knowledge retention for dental students.…”
Section: Introductionmentioning
confidence: 99%